RELIGIUSITAS PUISI KAMU TIDAK ISTIMEWA KARYA NATASHA RIZKY DAN REKOMENDASINYA SEBAGAI MODUL AJAR DI SMK - Aripatul Jamilah; Imam Muhtarom; Dewi Herlina Sugiarti (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to describe religiosity in the poetry collection Kamu Tidak Istinewa by Natasha Rizky and its recommendation as a teaching module in vocational schools. This research uses a qualitative approach and descriptive analysis method. The subject used in this research is the value of religiosity while the object is the collection of poems Kamu Tidak Istimewa by Natasha Rizky. Furthermore, the data collection techniques used are literature study and simak catat. Meanwhile, the data analysis techniques are data reduction, data presentation, and conclusion and verification. The results showed that the poem ‘Temanku’ contained two data, producing aspects of human intertwining with other humans, and the attitude of religiosity to help and love each other. Whereas in the poem ‘Maha Pencuru’ there are two data, producing aspects of human connection with God, and the attitude of religiosity to worship to further instil love for God. The final result of this research is used as a teaching module for learning poetry in vocational schools.